The Association between Fast Increase in Bone Turnover During the Menopause Transition and Subsequent Fracture - Shieh, Albert (J Clin Endocrinol Metab, 2019)
CONTEXT: Bone turnover increases rapidly during the menopause transition (MT) and plateaus above premenopausal levels in early postmenopause. It is uncertain whether higher bone turnover is associated with fracture in midlife women with near-normal bone mineral density (BMD). OBJECTIVE: Examine whether faster increases in bone turnover during the MT (2 years before to 2 years after the final menstrual period [FMP]), and greater bone turnover during early postmenopause (≥2 years after the FMP) are risk factors for subsequent fracture, accounting for BMD. DESIGN AND SETTING: The Study of Women’s Health Across the Nation, a longitudinal cohort study of the MT. PARTICIPANTS: A total of 484 women (initially pre- or early perimenopausal, who transitioned to postmenopause) with bone turnover (urine collagen type I N-telopeptide), BMD, and fracture data. MAIN OUTCOME MEASURE: Incident fracture after the MT. RESULTS: Adjusting for age, race/ethnicity, fracture before the MT, cigarette use, body mass index, and study site in Cox proportional hazards regression, each SD increment in the rate of increase in bone turnover during the MT was associated with 24% greater hazard of incident fracture in postmenopause (P = .008). Accounting for the same covariates, each SD increment in bone turnover during early postmenopause was associated with a 27% greater hazard of fracture (P = .01). Associations remained significant after controlling for MT rate of change and early postmenopausal level of BMD. CONCLUSION: Faster increases in bone turnover during the MT and greater bone turnover in early postmenopause forecast future fractures.